A structured approach for pharmaceutical pre-marketing safety surveillance - Tremmel, Lothar (Henry Stewart Talks, 2021)
Key-concepts in safety surveillance, Pre-marketing and post-marketing surveillance, Assessing drug-event relatedness via increased frequency analysis, The FDA’s final rule on IND safety reporting, Surveilling for unknown unknowns, Providing context and perspective to emerging suspected safety issues, The importance of interdisciplinary collaboration, The Aggregate Safety Assessment Plan (ASAP)